Poliamor, uma forma não exclusiva de amar: correlatos valorativos e afetivos. - Freire, Sandra Elisa de Assis (2013)
The main goal of this dissertation was to know in what extent the values, love and jealous explain the attitudes toward polyamory. It also aimed at developing a measure of self-report (explicit), Attitudes toward Polyamory Scale (ATPS) and an implicit measure (IAT-Monogamy/Polyamory) measure in order to evaluate such attitudes. Thus, it was conducted four empirical studies. Study 1 corresponded to the elaboration of the Attitudes toward Polyamory Scale (ATPS). Participants were 207 students from two private universities of João Pessoa (PB), with ages ranging from 18 to 50 (m = 25.7, sd = 7.19), most being male (56%). They answered a questionnaire divided in two parts. The first part had seven open questions, and the second, socio demographic questions. Participants answers were evaluated by automatic content analysis (ALCESTE). Two different classes were listed. In short, they revealed a comprehension of the problematic surrounding the polyamory dynamics as a romantic relationship. Study 2 presented the psychometric parameters of the proposed measure (ATPS). Participants were 261 undergraduate students from João Pessoa (PB), with ages ranging from 18 to 63 years (m = 30.1; sd = 9.80), most being female (57,5 %). The ATPS presented two components with internal consistency (Cronbach s alph) of .86 and .78, respectively. Reading the items content has allowed to define them as polyamory as a possibility of relationship and feelings regarding the polyamory . Study 3 describes how human values, the dimensions of polyamory and the factors of jealous explain attitudes toward polyamory; and, moreover, it aimed to test the two dimensional model of the ATPS. Participants of this study were 242 undergraduate students from the state of Piauí, with mean age of 23 years (sd = 5.28, amplitude of 18 to 50), most being female (64.2%). It was evident that the affective dimension, especially jealousy, had greater predictive power on explaining these attitudes; and that polyamory as a possibility of relationship was less conventional to people who engage socially accepted norms regarding romantic relationships, such as those guided by normative values. Results also confirmed the two factor structure of the ATPS. Finally, Study 4 sought to construct an implicit measure in order to evaluate attitudes toward polyamory, and analyze the relation between implicit and explicit measures of this construct. Two versions of the IAT-Monogamy/Polyamory were used. The pencil and paper version counted with the participation of 170 students from a public university from Piauí (PI), with mean age of 22 years (sd = 5.15), most being female (70%). In the computerized version, participants were 100 students from a public university of Piauí-PI, with mean age of 22 years (sd = 2.93). There were significant correlations between implicit and explicit measures, indicating that when people had favorable explicit attitudes toward polyamory, respectively, they expressed favorable implicit attitudes toward this form of relationship. However, for students, monogamy and polyamory were not presented on opposite sides, suggesting that people favorable to monogamy are not necessarily opposed to polyamory.